Pemanfaatan Instagram untuk Media Promosi dalam Meningkatkan Ketahanan UMKM bagi Forum Gerakan Terintegrasi Masyarakat Koperasi dan Usaha Mikro (Gerai Kopimi) Lamper Lor Semarang Selatan - Aria Hendrawan; Khoirudin Khoirudin; Vensy Vydia (Jurnal Surya Masyarakat, 2023)
This dedication was motivated by a request from one of the GERAI KOPIMI FORUM (Gerakan Terintegrasi Masyarakat Koperasi Dan Usaha Mikro) located in Lamper Lor, South Semarang, so that Lamper Lor, UMKM South Semarang could reach a wider market.  With the COVID-19 pandemic, product marketing must be transformed using internet media, due to the limited space for product marketing. USM community service team through the Community Service program will provide assistance to the UMKM Forum Gerai Kopimi Semarang Selatan using social media to promote their products more broadly. Armed with information technology knowledge, especially in the field of marketing using social media and product shooting techniques owned by the service team, it is hoped that they will be able to expand the reach of marketing their products. This activity will be carried out in several stages, First, conducting field surveys related to partner problems, Second, designing the most appropriate methods for utilizing social media for product marketing and designing the most suitable packaging designs for products so that they can increase the value of partner products. Third, conduct training for partners to optimize social media in marketing products. Fourth, evaluate the results of the training. The positive response was given by almost all participants who wanted to use the Instagram platform as a medium for promoting products of UMKM and felt satisfied with the training provided, so they wanted more training.